COMPARISON OF PHYSIOLOGICAL RESPONSES BETWEEN CONSCIOUS AND UNCONSCIOUS ICU PATIENTS AFTER RECEIVING AL-MA’TSURAT DHIKR THERAPY - Moch. Achwandi Achwandi; Zulfa Khusniyah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
ICU patients are vulnerable to physiological response alterations due to stress, anxiety, and disturbances in homeostasis. Spiritual-based non-pharmacological approaches, such as Al-Ma’tsurat dhikr therapy, have the potential to provide calming effects through auditory stimulation and modulation of the autonomic nervous system. This study aimed to analyze the physiological responses of conscious and unconscious ICU patients before and after the administration of Al-Ma’tsurat dhikr therapy and to compare the physiological responses between the two groups. This study employed a quasi-experimental design with a pretest–posttest approach. The study population consisted of all ICU patients treated during the study period, with a total sample of 60 respondents, comprising 30 conscious patients and 30 unconscious patients, selected based on predetermined inclusion and exclusion criteria. The intervention involved playing Al-Ma’tsurat dhikr recitations in the morning and afternoon. Physiological parameters measured included systolic and diastolic blood pressure, heart rate, and respiratory rate. Data analysis was conducted using the Wilcoxon Signed Rank Test and the Mann–Whitney test. The results showed that in conscious ICU patients, Al-Ma’tsurat dhikr therapy had a significant effect on reducing respiratory rate (p < 0.05). In unconscious ICU patients, the therapy significantly reduced systolic blood pressure, diastolic blood pressure, and respiratory rate, particularly during morning measurements (p < 0.05). Comparison between the two groups indicated that respiratory rate was the most consistently and significantly affected parameter. In conclusion, Al-Ma’tsurat dhikr therapy influences the physiological responses of both conscious and unconscious ICU patients, with the most consistent effect observed in the regulation of the respiratory system.